Strength Improvement of Cement Stabilized Soil by Binder Mineral Additive - T. Harianto; F. Sitepu; Jasrudin . (International Association of Lowland Technology, 2019)
The stability of the underlying soil significantly influences pavement construction for long-term performance. Subgrades often have a low bearing capacity in order to achieve adequate capacity under traffic loading. This study presents the strength and bearing capacity of the road pavement by utilization of a binder mineral powder for soil-cement stabilization. The Unconfined Compression Test (UCT) and California Bearing Ratio (CBR) test conducted at optimum moisture content (OMC) and maximum dry density (MDD). The dry-wet cycle (D-W) test also conducted to observe the strength behavior of the stabilized soil. The results show that the mix of the binder mineral and soil-cement, resulting in higher strength and bearing capacity. The strength characteristics of stabilized soil with binder mineral tend to decrease for the initial cycle slightly. In contrast to untreated soil, the strength significantly decreased by subjected to the wet-dry cycle test. These characteristics change of stabilized soil may lead to potential using of binder mineral as an additive for soil-cement stabilized.